Structural change in Thailand’s tobacco leaf exports: Implications of tobacco control in ASEAN countries - Jaroensathapornkul, Jirawat (Asian Journal of Agriculture and Rural Development, 2023)
The purpose of this research is to investigate the implications of tobacco control policies and measure how these have brought about structural changes in Thailand’s tobacco leaf exports. The methodology involved employing secondary data to estimate the econometrics model and then utilizing the Chow test. The findings showed that the estimates from the econometrics model reflect the income elasticity of the real export value of 6.621. In the Chow test, a statistically significant (at 0.05) structural change in Thailand’s tobacco leaf export was apparent when comparing the results before and after the first quarter of 2010. Furthermore, since 2010 the exports have shifted from the old market to other ASEAN countries, namely Indonesia, the Philippines, Malaysia, and Lao PDR. Concerning the practical implications, from a public health perspective, the results provide evidence for the efficiency of tobacco control policies and measures in European countries, the US, and Australia. On the other hand, they also pinpoint an area of improvement for tobacco control policies in ASEAN countries, and further investigation is required. From an economic perspective, Thai tobacco farmers need to be supported by the government during the transition period.